Rapid and Complete Biodegradation of Acrylic Acid by a Novel Strain Rhodococcus ruber JJ-3: Kinetics, Carbon Balance, and Degradation Pathways - He, Jinjia; Chen, Yi; Dai, Luyao; Yao, Jiachao; Mei, Yu; Hrynsphan, Dzmitry; Tatsiana, Savitskaya; Chen, Jun (Biotechnology and bioprocess engineering, 2020)
Acrylic acid is used in various industrial applications but inflicts harm to human health and causes environmental pollution. A new bacterium, identified as Rhodococcus ruber JJ-3, was isolated, which can degrade high concentrations of acrylic acid rapidly and completely. Experimental results showed that the strain can achieve complete degradation of 1000 mg·L −1 acrylic acid in 11 h under the following conditions: pH 7, temperature 35°C, and inoculation quantity 15%. A high concentration of acrylic acid (2000 mg·L −1 ) can be completely removed in 28 h. According to the Monod model, the maximum specific degradation rate ( v max ) and half saturation rate constant ( K S ) of the strain were 0.85 h −1 and 101.83 mg·L −1 , respectively. The results of carbon balance revealed that 54.6% carbon was assimilated by R. ruber JJ-3 as biomass, and 43.0% carbon was mineralized into CO 2 . Furthermore, glycerol and lactic acid were measured as intermediates, and the possible degradation pathway was proposed during the biodegradation of acrylic acid. These results suggested that R. ruber JJ-3 completely degrades acrylic acid and might have a potential environmental implication in the purification of acrylic acid-contaminated environments.